2021
DOI: 10.3390/biom11111652
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Metabolism in Brain-Heart Axis: New Challenge for the Therapy and Prevention of Alzheimer Disease. May Thioredoxin Interacting Protein (TXNIP) Play a Role?

Abstract: Alzheimer disease (AD) is the most frequent cause of dementia and up to now there is not an effective therapy to cure AD. In addition, AD onset occurs decades before the diagnosis, affecting the possibility to set up appropriate therapeutic strategies. For this reason, it is necessary to investigate the effects of risk factors, such as cardiovascular diseases, in promoting AD. AD shows not only brain dysfunction, but also alterations in peripheral tissues/organs. Indeed, it exists a reciprocal connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 129 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…Oxidative stress activates the NLRP3 inflammasome through the Thioredoxin-Interacting Protein (TXNIP) [ 12 ], an inhibitor of the ROS scavenger Thioredoxin, and promotes oxidative stress [ 13 ]. TXNIP links oxidative stress to inflammation, leading to cellular dysfunction and it is implicated in several diseases that are at risk for AD [ 14 ]. Although recent studies are suggesting a possible role of TXNIP in AD [ 15 18 ] there is no study investigating the effect of TXNIP in activating the microglial NLRP3 inflammasome in an AD contest.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress activates the NLRP3 inflammasome through the Thioredoxin-Interacting Protein (TXNIP) [ 12 ], an inhibitor of the ROS scavenger Thioredoxin, and promotes oxidative stress [ 13 ]. TXNIP links oxidative stress to inflammation, leading to cellular dysfunction and it is implicated in several diseases that are at risk for AD [ 14 ]. Although recent studies are suggesting a possible role of TXNIP in AD [ 15 18 ] there is no study investigating the effect of TXNIP in activating the microglial NLRP3 inflammasome in an AD contest.…”
Section: Introductionmentioning
confidence: 99%
“…RAGE promotes inflammation also by inducing the expression of Thioredoxin-Interacting Protein (TXNIP), which is an β-arrestincontaining protein that can bind to and inhibit the antioxidant protein thioredoxin (TXN), promoting oxidative stress (Perrone et al, 2009;Sbai et al, 2010). TXNIP is over expressed in the brain of AD patients and in several AD mice models and recent data suggest that it participates in AD pathophysiology (Melone et al, 2018;Nasoohi et al, 2018a,b;Wang et al, 2019;Tsubaki et al, 2020;Perrone and Valente, 2021;Zhang M. et al, 2021). TXNIP plays a key role in modulating the cell and body glucose homeostasis (Perrone and Valente, 2021).…”
Section: Role Of Drp1 In Admentioning
confidence: 99%
“…TXNIP is over expressed in the brain of AD patients and in several AD mice models and recent data suggest that it participates in AD pathophysiology (Melone et al, 2018;Nasoohi et al, 2018a,b;Wang et al, 2019;Tsubaki et al, 2020;Perrone and Valente, 2021;Zhang M. et al, 2021). TXNIP plays a key role in modulating the cell and body glucose homeostasis (Perrone and Valente, 2021). Notably, TXNIP plays a key role in activating the NLRP3 inflammasome (Schroder et al, 2010) and its association with NLRP3 has been shown also in AD (Li et al, 2019;Sbai et al, 2022).…”
Section: Role Of Drp1 In Admentioning
confidence: 99%
“…Neurodegenerative diseases are characterised by progressive atrophy and loss of neuronal function. Although several familiar forms of neurodegenerative diseases have been characterised by analysing the function of mutant genes, the relevance of altered metabolic function as a key factor promoting the onset and progression of sporadic neurodegenerative diseases is emerging [ 10 ]. In this context, mitochondrial alterations promote key events occurring during ageing and in neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%